Character Education in the Quran: Its Urgency and Implementation - Fauziah Zainudin (STAI Hubbulwathan Duri, 2023)
This paper aims to formulate the concept of character education (CE), describe the essence and existence of CE, and provide an overview of the urgency and implementation of CE in the Qur'an. Thus, the main study of this research is the insight of the Qur'an about CE. It focuses on the thematic interpretation in the type of qualitative research, mainly library research. Research data from commentary books were then analyzed using the science of interpretation approach with various interpretation techniques in analyzing verses about CE. The research findings show that the essence of CE refers to the personality of Rasulullah saw. who prioritizes good values through strategic steps, namely applying CE values informally, formally, and non-formally in the educational environment. The urgency of CE, according to the Qur'an is caused by a moral crisis and reduced public understanding of religious teachings that uphold the values of goodness and truth. The output of CE is the embodiment of a noble character which generates morals and ethics at the same time. This is illustrated in the character of a Muslim who is faithful and pious as well as muhsin. The implication of this research is that the existence of CE is a solution for solving problems in society, especially moral crises.